Leadership in Early Childhood Education and Care: Gender, Class, and Women who Care(s)? - Nolan, Geraldine Mary (Trinity College Dublin. School of Education. Discipline of Education, 2021)
The Irish Early Childhood Education and Care (ECEC) sector has undergone considerable change in the last decade, including introducing various leadership roles for the ECEC practitioner. Conversely, it is difficult to establish what principles underpin these roles, as there is a shortage of leadership research and training in the sector. This study explored how leadership was conceptualised, practised, the supports in place for leadership, and the potential leadership could hold in drawing together Irish ECEC practitioners to address their working conditions. A social feminism perspective informed this study; dual system theory (Eisenstein, 1979), and 50 ECEC stakeholders were interviewed (A qualitative interview study). The participants found it challenging to articulate the purpose of ECEC leadership in a sector where there were multiple understandings of leadership emanating from a network of disjointed government departments and organisations. Ultimately, most of the participants understood leadership as a relational, context-specific, and socially constructed activity. However, the ECEC practitioners' classed and gendered conceptualisation of care as a value position was incompatible with the remaining participants' commodified, educationalised, and intellectualised opinions of care. The lack of recognition and respect for "care" as an axiom and fundamental mode of praxis in ECEC had marginalised practitioner knowledge and weakened their confidence in articulating and positioning care as central to the purpose of ECEC and leadership. They considered care the antidote to the neoliberal care[less] sector, the missing link in prioritising the child over affordable childcare and highlighting the importance of their work and working conditions. Ultimately it was difficult to ascertain whether the ECEC practitioners' description of a caring and collaborative process involved leadership or leadership was part of a set of collaborative and participatory tools to do the work of questioning and reimaging ECEC and developing their working conditions.
APPROVED
Keywords: Leadership; ECEC Practitioner; Gender; Class; Care; Working Conditions